2018
DOI: 10.22159/ajpcr.2018.v11i6.24660
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oven and Microwave Drying on Polyphenols Content and Antioxidant Capacity of Herbal Tea From Strobilanthes Crispus Leaves

Abstract: Objective: This study aimed to evaluate the effect of oven and microwave drying on total phenolic content (TPC), total flavonoid content (TFC), and antioxidant capacity of unfermented and fermented tea developed from Strobilanthes crispus leaves.Methods: TPC and TFC were estimated using a spectrophotometric method, while antioxidant capacity was determined using ferric reducing antioxidant power assay and 2,2-diphenyl-1-picrylhydrazyl radical scavenging assay. Camellia sinensis (tea plant), that is, used for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…This finding is comparable with others who reported a similar trend of significant higher values of antioxidant activity along with total phenol and flavonoid [39]. Lasano et al [40] indicated a great association of antioxidant activity with TPC and TFC in unfermented Strobilanthes crispa tea. It has also been shown that in vitro antioxidant powers vary according to teas and antioxidant capacity and the content of total phenolics in tea is strongly correlated [23] as phenolic compounds are powerful chain breaking antioxidants that can directly contribute to antioxidative action [41].…”
Section: Discussionsupporting
confidence: 89%
“…This finding is comparable with others who reported a similar trend of significant higher values of antioxidant activity along with total phenol and flavonoid [39]. Lasano et al [40] indicated a great association of antioxidant activity with TPC and TFC in unfermented Strobilanthes crispa tea. It has also been shown that in vitro antioxidant powers vary according to teas and antioxidant capacity and the content of total phenolics in tea is strongly correlated [23] as phenolic compounds are powerful chain breaking antioxidants that can directly contribute to antioxidative action [41].…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, the microwave-dried B. tuldoides and B. vulgaris specimens in the current study recorded the highest FRAP yield. Similarly, Lasano et al [ 41 ] recommended microwaving fermented and unfermented Strobilanthes crispus tea to obtain preferable antioxidant capacities, including FRAP and DPPH. The antioxidant index proposed by the report might also be employed as a new marker in determining the optimal drying method for varying food products [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…In another study, microwave-dried blueberry leaves showed a higher TPC than oven-dried leaf samples [21]. The highest TPC was recorded in the Strobilanthes crispus tea leaves developed from microwave-dried leaves [22]. On the contrary, the total phenolic content of date fruit flesh decreased after microwave and conventional oven drying compared to the control sample [23].…”
Section: Total Phenolic Content Of Leptadenia Pyrotechnica Stemmentioning
confidence: 92%